2016
DOI: 10.1097/mbp.0000000000000187
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the neutrophil–lymphocyte ratio in newly diagnosed nondiabetic hypertensive patients with ascending aortic dilatation

Abstract: NLR as a marker of chronic low-grade inflammation may play a role in the pathogenesis of aneurysm of the ascending aorta in hypertensive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
1
12
1
Order By: Relevance
“…In the hypertension patients, the NLR value increased and positively correlated with hyperhomocysteinemia [19]. In the pathogenesis of aneurysm of the ascending aorta in hypertensive patients, NLR as a marker of inflammation may play an important role [20]. In patients with symptomatic intermediate carotid artery stenosis, NLR was increased and the increased NLR value was an independent variable for carotid artery plaques to become symptomatic [21].…”
Section: Discussionmentioning
confidence: 99%
“…In the hypertension patients, the NLR value increased and positively correlated with hyperhomocysteinemia [19]. In the pathogenesis of aneurysm of the ascending aorta in hypertensive patients, NLR as a marker of inflammation may play an important role [20]. In patients with symptomatic intermediate carotid artery stenosis, NLR was increased and the increased NLR value was an independent variable for carotid artery plaques to become symptomatic [21].…”
Section: Discussionmentioning
confidence: 99%
“…Hypertensive patients with high homocysteine(HCY) had increased NLR and it positively correlated with HCY but not with blood pressure [24]. Also, there was a statistically significant positive correlation between the ascending aortic diameter and NLR ( r  = 0.524, P  < 0.001), which indicated that it plays a role in the pathogenesis of aneurysm of the ascending aorta in hypertensive patients [25]. In addition, hypertensive patients with diastolic dysfunction had higher values of NLR compared with subjects without diastolic dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…[10] Cem O et al found that NLR is a marker of chronic low grade inflammation and play a role in the pathogenesis of aneurysm of the ascending aorta in hypertensive patients. [16] This studies showing that hypertensives have higher NLR, which has been demonstrated to have the greatest predictive power of death, myocardial infarction and high risk for coronary artery disease and it's an independent predictor of long-term mortality. [17] Research has shown that increased PLR value without absolute thrombocytosis is associated with thrombosis and inflammation, which might be due to an increase in platelet activity.…”
Section: Discussionmentioning
confidence: 90%